If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2x + -1 + -3 Reorder the terms: y = -1 + -3 + 2x Combine like terms: -1 + -3 = -4 y = -4 + 2x Solving y = -4 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -4 + 2x
| (5x^2)*3x= | | 3x*x=4.6 | | 12x+5y=315 | | 49+8x=15x | | (-3x-12)(5x-1/6) | | 0.5b+b=2000000 | | 3x*cos(x)= | | 5x^2+17y=0 | | 40+2*x+x=0 | | 2*(3-2x)=4-x | | 40*2*x*x=0 | | 4k-36=-12 | | 13p+17q+p-4q-7p=0 | | 6t^2+13t-7=0 | | 2x+6x-5=0 | | 7x+14-7=28+7 | | G(x)=-5x+30 | | 6x/21x7x/18 | | 15-m/4=5 | | 2*(3x+5y)=3*(8y-x)+21 | | 23/18-4/9 | | ?/192=3/? | | 7x+4=8x+-17 | | ?/129=3/? | | 8x+4=7x-17 | | 7x-17=8x+4 | | -10k-24=2k | | -63=16.8k-12.6 | | y=8E-05x-2.917 | | 3t^2-9t+24=0 | | 7x=10x-9 | | 0.3x+0.6=0.5x |